STUDY OF THE IMPACT OF HEALTH FILMS PRODUCED BY 'MADHYA PRADESH MADHYAM', AN INITIATIVE OF THE PUBLIC RELATIONS DEPARTMENT- A QUANTITATIVE RESEARCH - Vijayvargiya, Sanjay; Srivastava, Sandeep Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This quantitative research paper analyzes the impact of health films produced by 'Madhya Pradesh Madhyam', an agent of social change of the Public Relations Department of the Government of Madhya Pradesh. The main objective of this study is to assess the effectiveness of these films, particularly to understand the role of public relations media in increasing health awareness, bringing about behavioral change and dissemination of health information. Data were collected through structured questionnaires and interviews from 200 respondents (100 males and 100 females) from Bhopal. Analysis using statistical tools such as SPSS and Excel concluded that these films play a significant role in promoting health awareness and behaviour change. The results of the study also revealed that the impact of these films was higher among women, leading to health awareness and positive behaviour change among them. This research provides useful suggestions to policy makers and health organisations to increase the reach and effectiveness of health communication campaigns.